Botanical composition and carrying capacity of forage along the roadsides in the highlands of Bandung Regency - Suryanah, Sari; Sinta Sri Rahayu; Syifa Nurjannah; Nilawati Widjaya; Hilman Permana, (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2025)
Forage is the primary feed source for ruminant livestock, especially dairy cattle, as it provides essential nutrients for productivity. However, limited forage availability due to land conversion and seasonal changes has encouraged farmers to utilize field grasses, including roadside vegetation, as an alternative feed source. This study aimed to determine the botanical composition and carrying capacity of forage along the roadsides in the highlands of Bandung Regency. The sampling method used was purposive sampling, which involved deliberately selecting research locations through direct field surveys for data and sample collection. Sampling was conducted in five districts in the highlands of Bandung Regency—Ciwidey, Rancabali, Pangalengan, Cimaung, and Arjasari—with ten sampling plots in each district, resulting in a total of 50 plots. Sampling used a quadrat measuring 1 m × 1 m, which was placed randomly. Data were analyzed both qualitatively and quantitatively. The results showed that there were 72 botanical species, with Galinsoga parviflora being the most dominant species based on frequency of occurrence. At the same time, Pennisetum clandestinum was the most dominant species based on forage production. Based on biomass proportion, grasses dominated at 77.32%, legumes at 1.02%, and weeds at 21.66%. The carrying capacity of the roadsides in the highlands of Bandung Regency was 0.92 LU/ha/year, with forage production of 4.93 tons DM/ha/year, indicating that the roadside areas can support approximately one mature dairy cow, or two heifers, or four calves. The roadside in Rancabali District had the highest forage production, reaching 7.70 tons DM/ha/year with a carrying capacity of 1.40 LU/ha/year.